2018
DOI: 10.1097/ede.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to Air Pollution and Risk of Acute-onset Placental Abruption

Abstract: This case-crossover study showed evidence of an association between short-term ambient air pollution exposures and increased abruption risk of acute onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Our findings are consistent with our earlier work which demonstrated an association of PM 2.5 with a severe smoke event resulting from a coal mine fire in regional Victoria, Australia and increased likelihood of GDM [27]. To our knowledge, only three studies have explored maternal exposure to PM 2.5 and NO 2 in relation to placental abruption, with all reporting an increased likelihood of abruption with greater exposure [11][12][13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with our earlier work which demonstrated an association of PM 2.5 with a severe smoke event resulting from a coal mine fire in regional Victoria, Australia and increased likelihood of GDM [27]. To our knowledge, only three studies have explored maternal exposure to PM 2.5 and NO 2 in relation to placental abruption, with all reporting an increased likelihood of abruption with greater exposure [11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis of 11 studies exploring NO 2 , nitrogen oxides, ozone and sulfur dioxide only found an association between second trimester PM 2.5 and first and second trimester NO x exposure and GDM [10]. Only a handful of studies have specifically explored ambient air pollution and placental abruption; with all three studies finding an adverse association [11][12][13]. Synthesising findings is challenging owing to the relatively limited evidence base, various pollutants studied, various ranges of exposure (high-level vs. low-level), various periods of exposure (whole of pregnancy, trimester-specific or days prior to labour) and definition of outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Asian dust exposure in the study may have been a surrogate marker of high exposure to particulate matter. Indeed, a case‐crossover study based on birth records and hospital discharge data in New York from 2008 to 2014, reported the increased odds of placental abruption with exposure to fine particulate matter . Exposure to particulate matter may lead to acute biological responses, such as inflammation and ischaemia, which appear capable of extending into the uterus .…”
Section: Discussionmentioning
confidence: 99%
“…A study in New York also reported a higher odds of abruption (1190 cases) on lag days 3 (OR 1.19, 95% CI 0.98, 1.43), lag day 4 (OR 1.21, 95% CI 1.01, 1.46), and lag day 5 (OR 1.17, 95% CI 1.03, 1.33) in relation to every 10 μg/m 3 in ambient fine particulate matter (PM 2.5 ). Similarly, the odds of abruption was also increased on lag day 3 (OR 1.16, 95% CI 0.98, 1.37), lag day 4 (OR 1.19, 95% CI 1.02, 1.39), and lag day 5 (OR 1.16, 95% CI 1.05, 1.27) with every 5 ppb increase in exposure to NO 2 . Placental abruption has been conceptualised as an ischaemic placental disorder, and so, it is worth noting that some of the recent findings on abruption mirror the heightened risk in ischaemic cardiovascular events following transient exposure to physical, chemical, and psychological stressors …”
Section: Commentmentioning
confidence: 96%
“…Outbursts of anger have been well studied as an immediate precipitant of ischaemic cardiovascular events, but studies have only recently begun to investigate immediate precipitants, or triggers, of abruptions of acute onset. Prior research on abruption has assessed the short‐term risk following exposures to higher levels of ambient air pollution and intense physical exertion . Anecdotal evidence also suggests that acute mental stress may precipitate abruption, but there have been no studies examining the acute risk of abruption immediately following episodes of anger.…”
Section: Introductionmentioning
confidence: 99%